BS EN 12608-2. Unplasticized poly(vinyl chloride) (PVC-U) profiles for the fabrication of windows and doors. Classification, requirements and test methods. Part 2. PVC-U profiles covered with foils bonded with adhesives (18th August 2022) - British Standards Institution,
No abstract available